Pemikiran Sosiologi Ekonomi Islam - Nurjanah, Nurjanah (ITB AAS INDONESIA Surakarta, 2023)
Abstract This study carries the thought of Islamic economic sociology as an approach that combines the principles of Islamic economics with social analysis in understanding economic phenomena in the context of Muslim societies. The purpose of this research is to identify the main issues in Islamic economic sociology thinking, explain the research objectives, present the methods/approaches used, and summarize the research results. This research identifies several main issues in Islamic economic sociology thinking, including distributive justice, economic and environmental sustainability, and ethical values in business. This research aims to deepen understanding of this thinking and its relevance in dealing with contemporary economic challenges. The method/approach used is an analysis of literature and classical Islamic texts, as well as relevant empirical research. The results of the study show that the sociological thinking of Islamic economics makes an important contribution to understanding economic phenomena in Muslim societies. Islamic principles, such as distributive justice, sustainability, and ethical values, form the foundation for building an inclusive and sustainable economic model. This research also uncovers important issues such as social inequality, gender inequality, and environmental impact on economic activity. The results of the study show that Islamic economic sociology has the potential to provide a comprehensive view of overcoming social and economic challenges in Muslim societies. This research concludes that this approach can be a source of inspiration for sustainable economic policies, as well as promoting justice, balance, and prosperity for all members of Muslim society.